Nanoformulations of Ursolic Acid: A Modern Natural Anticancer Molecule - Wang, Longyun; Yin, Qianqian; Liu, Cun; Tang, Ying; Sun, Changgang; Zhuang, Jing (Frontiers in Pharmacology, 2021)
Background: Ursolic acid (UA) is a natural pentacyclic triterpene derived from fruit, herb, and other plants. UA can act on molecular targets of various signaling pathways, inhibit the growth of cancer cells, promote cycle stagnation, and induce apoptosis, thereby exerting anticancer activity. However, its poor water-solubility, low intestinal mucosal absorption, and low bioavailability restrict its clinical application. In order to overcome these deficiencies, nanotechnology, has been applied to the pharmacological study of UA. Objective: In this review, we focused on the absorption, distribution, and elimination pharmacokinetics of UA in vivo, as well as on the research progress in various UA nanoformulations, in the hope of providing reference information for the research on the anticancer activity of UA. Methods: Relevant research articles on Pubmed and Web of Science in recent years were searched selectively by using the keywords and subheadings, and were summarized systematically. Key finding: The improvement of the antitumor ability of the UA nanoformulations is mainly due to the improvement of the bioavailability and the enhancement of the targeting ability of the UA molecules. UA nanoformulations can even be combined with computational imaging technology for monitoring or diagnosis. Conclusion: Currently, a variety of UA nanoformulations, such as micelles, liposomes, and nanoparticles, which can increase the solubility and bioactivity of UA, while promoting the accumulation of UA in tumor tissues, have been prepared. Although the research of UA in the nanofield has made great progress, there is still a long way to go before the clinical application of UA nanoformulations.